A model of classroom social climate, foreign language enjoyment, and student engagement among English as a foreign language learners - Mohammad Hosseini, Hamed; Fathi, Jalil; Derakhshesh, Ali; Mehraein, Sepideh (Frontiers in Psychology, 2022)
With the advent of positive psychology in second language (L2) learning, some researchers have undertaken empirical studies to explore emotional variables affecting L2 learning and how positive emotions can enhance engagement of L2 learners. As an attempt to contribute to this research domain, this project sought to test a model of student engagement based on classroom social climate (CSC) and foreign language enjoyment (FLE) among English language learners in Iran. A sample of 386 intermediate EFL learners took part in this survey by completing the online battery of questionnaires. Structural Equation Modeling (SEM) was employed for the analysis of the gathered data. The results showed that both CSC and FLE were the significant predictors of student engagement, with FLE acting as a stronger predictor. Furthermore, CSC exerted a slight influence on FLE. The findings might offer remarkable implications for L2 practitioners.